2019
DOI: 10.1016/j.ijhm.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and outcome of job embeddedness: Evidence from four and five-star hotels

Abstract: The present study explores the antecedents and outcome of job embeddedness. The antecedents are: level of control over work hours and felt obligation. The outcome is proactive customer service performance. Using self-administered questionnaires, 163 paired responses were gathered from frontline employees and their supervisors/managers in 16 hotels/resorts with a rating of four and five stars in Malaysia. Frontline employees responded to the questions on level of control over work hours, felt obligation and job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 51 publications
0
24
0
2
Order By: Relevance
“…Meta-analytics of data of various studies also suggest that JE has a reliable negative impact on turnover intention (Jiang et al, 2012). Several other recent studies have established that improved JE tends to reduce VTOI in organizations (Reitz, 2014;Chan et al, 2019).…”
Section: Job Embeddedness (Je) and Voluntary Turnover Intention (Vtoi)mentioning
confidence: 89%
“…Meta-analytics of data of various studies also suggest that JE has a reliable negative impact on turnover intention (Jiang et al, 2012). Several other recent studies have established that improved JE tends to reduce VTOI in organizations (Reitz, 2014;Chan et al, 2019).…”
Section: Job Embeddedness (Je) and Voluntary Turnover Intention (Vtoi)mentioning
confidence: 89%
“…Specifically, because workload proved to be an influential job stressor leading to hotel employees' emotional exhaustion, any methods to reduce excessive workload are strongly recommended under managerial attention. Therefore, firstly, as hospitality jobs are characterized by long, unsocial working hours in variable shifts, including nights and weekends (Chan et al, 2019;Ch-K. & Ko, 2009), employees should have more flexibility in setting their own working schedule, and their preferences in this regard should be then incorporated into the schedule (Schiffinger & Braun, 2020). Secondly, given seasonality in hospitality jobs and high peaks in demand, hotel operational departments should be optimally staffed to avoid excessive workload and time pressure (Schiffinger & Braun, 2020); otherwise, the pressure to perform well in understaffed situations makes the work particularly stressful and exasperating for employees.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, although highly skilled and attentive hotel employees are important to succeed (Nain, 2018), they are especially exposed to stress due to the characteristics of their jobs (Hwang et al, 2014), such as the 24/7 nature of work, antisocial and long working hours, unpredictable shifts, few breaks, excessive workload, etc. All this builds up especially high levels of stress among employees (Chan et al, 2019;Haldorai et al, 2019;Sampson & Akyeampong, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analytic data of various studies also suggest that JE has a reliable and adverse effect on TOI (Jiang et al, 2012). Other studies have found that enhancing JE tends to reduce voluntary TOI (VTOI) in organizations (Chan et al, 2019;Reitz, 2014).…”
Section: Theory and Implications Of Jementioning
confidence: 94%